2009
DOI: 10.4103/0974-2077.58521
|View full text |Cite
|
Sign up to set email alerts
|

Q-switched Nd:YAG laser to treat nevomelanocytic nevi

Abstract: Background:Q-switched Nd:YAG laser, a melanin pigment-specific laser was used to treat melanocytic nevi in Indian patients.Objective:To assess the clinical response of nevi to Q-switched Nd:YAG laser of 1064 nm wavelength.Materials and Methods:Nineteen patients received an average of 2.57 treatments with Q-switched Nd:YAG laser of 1064 nm wavelength, repetition rate of 10 Hz, 10 nanoseconds pulse width, and spot size of 4 mm to 6 mm with a fluence ranging from 4 to 9.7 joules/cm2. The clinical end point of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
1
2
0
1
Order By: Relevance
“…None of the study participants had their tattoo removed in 1 or 2 sittings Table 5 . Present study achieved success in almost 3 4 patients in tattoo removal treatment which quite comparable with similar study done by Jones A et al, 18 Fergusion & August et al, 20 Parasramani SG et al, 8 and Vibhagool et al 31 Contrast result was found in similar study done by Ho WS et al, 27 Aurangabadkar S et al, 16 Wang ECE et al, 15 Reda et al, 34 Westerhof et al, 32 Baba et al 33 and Kim YJ et al 24 Success rate of tattoo removal is depending up on site, number, type, type of treatment, number of session, skin type, amount of ink used in tattoo, color of tattoo and age of tattoo. 14 Table 6 compares the efficacy of fluence 7 J/cm 2 vs 9 J/cm 2 of ND: YAG laser in amateur tattoo removal at different sessions.…”
Section: Resultssupporting
confidence: 90%
“…None of the study participants had their tattoo removed in 1 or 2 sittings Table 5 . Present study achieved success in almost 3 4 patients in tattoo removal treatment which quite comparable with similar study done by Jones A et al, 18 Fergusion & August et al, 20 Parasramani SG et al, 8 and Vibhagool et al 31 Contrast result was found in similar study done by Ho WS et al, 27 Aurangabadkar S et al, 16 Wang ECE et al, 15 Reda et al, 34 Westerhof et al, 32 Baba et al 33 and Kim YJ et al 24 Success rate of tattoo removal is depending up on site, number, type, type of treatment, number of session, skin type, amount of ink used in tattoo, color of tattoo and age of tattoo. 14 Table 6 compares the efficacy of fluence 7 J/cm 2 vs 9 J/cm 2 of ND: YAG laser in amateur tattoo removal at different sessions.…”
Section: Resultssupporting
confidence: 90%
“…Parasramani ve ark. 19 hastada nevomelanositik nevüslerin tedavisinde Q-anahtarlı Nd:YAG lazer kullanmışlar ve hastaların 11'inde %50 ve üzerinde düzelme izlemişlerdir (spot büyüklüğü: 3-6 mm, enerji akımı: 4,2-9,7 J/cm 2 , atım süresi: 10 ns, atım hızı: 10 Hz) 36 . Nevoselüler nevüslerde izlenen pigment yapısı diğer pigmente deri lezyonlarından farklılık göstermektedir.…”
Section: Nevoselüler Nevüslerunclassified
“…6 Pigment-specific QS lasers like QS ruby, alexandrite, and Nd: YAG lasers have also been used, but their effectiveness is inconsistent. 7 Nanosecond-pulsed QS lasers can target and disrupt individual pigment-containing cells through selective photothermolysis, but they cannot effectively treat groups of nevomelanocytes. 7 Depending solely on QS lasers is insufficient for complete nevus removal.…”
mentioning
confidence: 99%
“…7 Nanosecond-pulsed QS lasers can target and disrupt individual pigment-containing cells through selective photothermolysis, but they cannot effectively treat groups of nevomelanocytes. 7 Depending solely on QS lasers is insufficient for complete nevus removal. In addition, QS lasers often cause pigment changes post-treatment because of photomechanical damage around the treated area and direct stimulation of melanin in people with darker skin tones.…”
mentioning
confidence: 99%